Establishing an Assessment Criteria System for Architectural Heritage of Colonial Educational Buildings in Hanoi - Tran, Quoc-Bao; Hoang, Thai Hoc; Nguyen, The-Quan (International Journal of Sustainable Construction Engineering and Technology, 2021)
A number of educational buildings were built up by the French in Hanoi during their dominance. Most of these buildings still exist in the downtown area and have become an integral part of the valuable heritage, and their preservation is increasingly imperative. To preserve and promote more efficiently the values of the colonial building heritage assets, there is a need of a set of criteria for an assessment and classification. This paper presents the development of an assessment criteria system for the architectural heritage of colonial educational buildings in Hanoi. According to the proposals, colonial educational buildings can be classified into three groups of Special Value, Notable Value, Average Value. A set of criteria including factors related to both the internal and external values of these buildings have been proposed and validated with expert judgements. Each criterion then is incorporated with a set of scores showing the value it can bring to a colonial educational building to be assessed. The set of criteria and their scores can be used by the city authority to establish regulations to preserve and promote heritage values of the colonial educational buildings in Hanoi.